Single item to assess for worry for cancer: Initial evidence of validity and reliability [Ítem único para valorar la preocupación por el cáncer: evidencias iniciales de validez y confiabilidad] - Caycho-Rodríguez, Tomás (2019)
ABSTRACT Objective To translate into Spanish and evaluate the evidence of content validity, construct validity and reliability of the Cancer Worry Chart as a single item measure of worry for cancer. Method The Spanish translation of the Cancer Worry Chart was done with the back-translation procedure. The participants were 165 healthy people with a family history of cancer who responded to the Cancer Worry Chart and the Cancer Worry Scale (CWS). Results Translation back-translation allows a Spanish version of the Cancer Worry Chart whose content is clear, coherent and relevant (V ˃ .70). Evidence of construct validity is reported based on 3 criteria: a) an adequate adjustment of the one-dimensional model formed by the Cancer Worry Chart and the items of the CWS performed with the structural equations method (χ2S-B = 23.38; df = 14; χ2S-B/df = 1.67; CFI = .988; RMSEA = .064); b) a significant correlation between the Cancer Worry Chart and the CWS (r= .76 [IC95%: .68-.90]); c) ascending averages in the CWS score as the groups formed by each response option of the Cancer Worry Chart express a greater degree of worry (F = 55.72; P = .000; ω2 = .57). The reliability of the Cancer Worry Chart is above what is recommended (αsingle item = .84). Conclusion The Spanish version of the Cancer Worry Chart showed satisfactory evidence of content validity, construct validity and reliability to measure, briefly, quickly and generally, the worry for cancer in healthy people with a family history of cancer.